Protective Alzheimer's disease-associated APP A673T variant predominantly decreases sAPPβ levels in cerebrospinal fluid and 2D/3D cell culture models - Rebekka Wittrahm; Mari Takalo; Teemu Kuulasmaa; Petra M. Mäkinen; Petri Mäkinen; Saša Končarević; Vadim Fartzdinov; Stefan Selzer; Tarja Kokkola; Leila Antikainen; Henna Martiskainen; Susanna Kemppainen; et al. (Neurobiology of Disease, 2023)
The rare A673T variant was the first variant found within the amyloid precursor protein (APP) gene conferring protection against Alzheimer's disease (AD). Thereafter, different studies have discovered that the carriers of the APP A673T variant show reduced levels of amyloid beta (Aβ) in the plasma and better cognitive performance at high age. Here, we analyzed cerebrospinal fluid (CSF) and plasma of APP A673T carriers and control individuals using a mass spectrometry-based proteomics approach to identify differentially regulated targets in an unbiased manner. Furthermore, the APP A673T variant was introduced into 2D and 3D neuronal cell culture models together with the pathogenic APP Swedish and London mutations. Consequently, we now report for the first time the protective effects of the APP A673T variant against AD-related alterations in the CSF, plasma, and brain biopsy samples from the frontal cortex. The CSF levels of soluble APPβ (sAPPβ) and Aβ42 were significantly decreased on average 9–26% among three APP A673T carriers as compared to three well-matched controls not carrying the protective variant. Consistent with these CSF findings, immunohistochemical assessment of cortical biopsy samples from the same APP A673T carriers did not reveal Aβ, phospho-tau, or p62 pathologies. We identified differentially regulated targets involved in protein phosphorylation, inflammation, and mitochondrial function in the CSF and plasma samples of APP A673T carriers. Some of the identified targets showed inverse levels in AD brain tissue with respect to increased AD-associated neurofibrillary pathology. In 2D and 3D neuronal cell culture models expressing APP with the Swedish and London mutations, the introduction of the APP A673T variant resulted in lower sAPPβ levels. Concomitantly, the levels of sAPPα were increased, while decreased levels of CTFβ and Aβ42 were detected in some of these models. Our findings emphasize the important role of APP-derived peptides in the pathogenesis of AD and demonstrate the effectiveness of the protective APP A673T variant to shift APP processing towards the non-amyloidogenic pathway in vitro even in the presence of two pathogenic mutations.